Gender issues in the Tuvan Internet Discourse - Borgoiakova, Tamara G.; Lopsan, Alimaa P. (The New Research of Tuva, 2024)
The article analyzes the constants, transformations and problem areas of gender relations in the Republic of Tuva, identified on the Tuvan-language Internet. The materials for the analysis were the texts of posts and their discussions within the framework of five communities on the VKontakte social network, as well as online versions of articles by the republican newspaper “Shyn” (in Tuvan) and for comparison “Tuvinskaya Pravda” / “Tuvan Truth” (in Russian). The most pressing issues and orientations of gender culture in the “living” representation of modern native speakers of the Tuvan language are identified. The tendencies of transformation of gender roles in a contradictory relationship with the preservation of traditional ideas about the social relations of gender in Tuvan traditional culture are revealed. The implementation of the principles of gender equality is reflected in discursive practices about Tuvan women — financially independent, self-sufficient, providing for themselves and their families, and men adopting a modern gender culture based on social equality of the sexes. The increase in the social status of women, their professional and business success has not changed the stability of stereotypical ideas about gender hierarchy and the assignment of household duties mainly to women for cleaning, childcare, cooking, etc. Problem areas of marital and family relations are associated with alcoholism, abuse, lack of material wealth, a tendency to dependency and infidelity. The lexical and stylistic features of different types of discourse, including literary and colloquial forms of the modern Tuvan language, are revealed. Notable features of Tuvan social media discourse include the active presence of profanity. The official segment of the republic’s media revealed a higher degree of idealization of traditional images of men and women and their gender roles in the newspaper “Shyn” and a higher level of critical coverage of gender relations, combined with the dominance of a positive representation of successful men and women of the Republic of Tuva in “Tuvinskaya Pravda”.